Green coal and lubricant via hydrogen-free hydrothermal liquefaction of biomass - Maojiong Cao; Reaihan E; Changbin Yuan; Lasse Aistrup Rosendahl; Yuanhui Zhang; Charles Chunbao Xu; Yulong Wu; Deliang Kong; Yingxian Wang; Jiaming Li; Zhidan Liu (Nature Communications, 2025)
Abstract Biocrude derived from biomass via hydrothermal liquefaction (HTL) is a sustainable substitute for petroleum to obtain energy and biochemicals. Upgrading biocrude inevitably faces the trade-off between consuming large amounts of hydrogen via hydrotreating and high yield of solid residue without additional hydrogen. In this work, we report a non-hydrogenated refinery paradigm for nearly complete valorization (~90%), via co-generating green coal and bio-lubricant. The obtained green coal has higher heating values comparable to commercial coals, with a lower fuel ratio and reduced ash content. Viscosity of upgraded vacuum distillate is comparable to that of a lubricant oil. A life cycle assessment confirms 28% reduction in greenhouse gas emission and 35% reduction in energy input of this paradigm compared with conventional hydrotreating biorefinery. This approach presents an environmentally friendly, safe and convenient paradigm for biocrude refining from huge biowaste towards carbon-neutral society.